Is there association between epicardial obesity and the severity of coronary artery atherosclerosis?. (14th October 2021) - Polyakova, E A; Baranova, E I; Shlyakhto, E V
Abstract: Background: To assess the diagnostic capabilities of the ultrasound method for estimation of the epicardial fat (EF) and evaluate the association of the thickness of EF and the severity of coronary atherosclerosis in coronary heart disease (CHD) patients. Methods: 461 people (age Me 58 years, Q1=52; Q3=64) were examined: 182 patients with CHD (age Me 61 years, Q1=56; Q3=66; 72% men), 279 control patients without CHD, undergoing heart valve surgery (age Me 55 years, Q1=51; Q3=59; 51% men). The severity of coronary artery lesions was assessed according to the current 2013 ESC Guidelines (>50% for the left main coronary artery and >70% for other coronary arteries). Coronary angiography, heart computer tomography (CT), echocardiography (ECHO) were estimated. Statistical data analysis (SPSS, version 17.0, USA). Results: In CHD patients the volume of EF (heart CT) was significantly higher than in patients without CHD (167.0 cm 3 (128, 9; 167, 1) and 89.1 cm 3 (62, 7; 102, 7), z=−7.060, p<0.001). The thickness of EF in the area of atrioventricular sulcus (according to the ECHO) most closely corresponds to the volume of EF (according to heart CT), ρ=0.731, p<0.001. According to multiple linear regression analysis, it was found that in patients with CHD, an increase in age by 1 year is associated with an increase in the volume of EF by 1.4 cm 3 (95% CI from 1.0 to 1.9). The volume of EF in CHD patients is meen 56.7±3.1 cm 3 (95% CI from 46.6 to 66.8) more than in patients without CHD. The correlation between the number of coronary arteries affected by atherosclerosis and the values of the parameters characterizing the EF was not revealed. Conclusion: The volume of epicardial fat measured by cardiac CT in patients with CHD is greater than epicardial fat volume measured in subjects without ischemic heart disease. The volume of epicardial adipose tissue measured by heart CT in patients with CHD increases with age. The number of coronary arteries affected by atherosclerosis in CHD patients does not depend on the thickness and volume of epicardial adipose tissue. Funding Acknowledgement: Type of funding sources: Other. Main funding source(s): The study has been supported by the grant from the Ministry of Science and Higher Education of the Russian Federation